1994
DOI: 10.1126/science.7973733
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Mismatched Microsatellite DNA Sequences by the Human MSH2 Protein

Abstract: Alteration of the human mismatch repair gene hMSH2 has been linked to the microsatellite DNA instability found in hereditary nonpolyposis colon cancer and several sporadic cancers. This microsatellite DNA instability is thought to arise from defective repair of DNA replication errors that create insertion-deletion loop-type (IDL) mismatched nucleotides. Here, it is shown that purified hMSH2 protein efficiently and specifically binds DNA containing IDL mismatches of up to 14 nucleotides. These results support a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(84 citation statements)
references
References 36 publications
5
79
0
Order By: Relevance
“…In this case, some form of post replication repair will be needed to correct the error. It has been previously shown that the human homologue of E. coli MutS, hMSH2, can bind to duplex oligonucleotides containing short (5-16 nucleotides) insertion/deletion loops (30). This repair protein has also been demonstrated to bind PCNA (29,67).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, some form of post replication repair will be needed to correct the error. It has been previously shown that the human homologue of E. coli MutS, hMSH2, can bind to duplex oligonucleotides containing short (5-16 nucleotides) insertion/deletion loops (30). This repair protein has also been demonstrated to bind PCNA (29,67).…”
Section: Figmentioning
confidence: 99%
“…PCNA is also thought to interact with human homologues of E. coli MutS and MutL (hMSH-2 and hMLH1, respectively; (29)). hMSH2 specifically binds single base pair mismatches as well as short loops of 4 -16 nucleotides (30,31). Other proteins that interact with PCNA include DNA ligase I (32), Xeroderma pigmentosum G (33), and p21 (Cip1) (34,35).…”
mentioning
confidence: 99%
“…Small loops, bulges, or kinked DNA occur frequently in DNA, and provide signals for p53 recognition (4-7), recombination (8,9), and/or most often removal by the mismatch repair system (10)(11)(12)(13)(14). Two heterodimeric mismatch recognition complexes, MSH2/MSH6 and MSH2/MSH3, operate in mammals with distinct, but overlapping specificities (12)(13)(14).…”
mentioning
confidence: 99%
“…A highlight was the demonstration with Arnold Levine at Princeton University that p53 binds to bulged bases and Holliday junctions (39), a possibility that came out of our studies of RecA protein binding to DNA containing bulged bases (40). Work on mismatch repair has involved ongoing collaborations with Paul Modrich at Duke University (41,42), Richard Kolodner at the University of California, San Diego (43,44), and Rick Fishel at Ohio State University (45,46), where these methods have revealed the binding of mismatch repair factors to DNA, as well as DNA looping by MutS (42). These studies paralleled work on the binding of key factors in signal transduction between sites of damage and the damage response pathways with Aziz Sancar at the University of North Carolina (47,48).…”
Section: Visualizing Proteins That Bind To Unusual Dna Structuresmentioning
confidence: 99%